A generalized robust decentralized control methodology for a class of interconnected nonlinear systems subject to uncertainties and disturbances. (November 2016) - Zhang, Chuanlin; Li, Hui
Abstract: This paper studies the problem of robust decentralized control for a class of large-scale interconnected systems subject to uncertainties and disturbances via a generalized output feedback control method. First, a generalized extended state observer is constructed separately for each subsystem with less dependence of the precise system information and structure. Second, an explicit formula of the easy-transplantable decentralized robust control law is presented with an active compensation of disturbance. Moreover, the proposed methodology is extended to the sampled-data control case without any additional assumptions and hence will ease the practical implementations. It is shown that by a delicate analysis procedure of both continuous-time and hybrid scenarios, the closed-loop system can be rendered semi-globally asymptotically stable only using decentralized output feedback anti-disturbance controller. Numerical simulations show the efficiency of the proposed method.